Pengaruh Latihan Power Otot Lengan Terhadap Kemampuan Chest Pass Bola Basket SMP Tri Bhakti Pekanbaru (Department of Physical Education, Sport, Health and Recreation, 2016)
This study aims to find out about how much influence of muscle power training arm of the ability ofbasketball Chest passjunior high school students’ extracurricular son of tri bhakti pekanbaru. This studyis an experiment that uses the Chest pass test before and after exercise. The study was conducted of TriBhakti Pekanbaru. The research data gathered through the data Pree and post test and treated with t-testtechnique. The analysis shows encountered in the study between Pree test and post test students’ abilityto Chest pass significance level). Based on these data it is clear that the alternative hypothesis is acceptedthat are significant influence of muscle power training arm of the ability of basketball Chest pass juniorhigh school students’ extracurricular Tri Bhakti Pekanbaru. Thus the results of research done to say thatexercise variation influence of muscle power training arm of the ability of basketball Chest pass juniorhigh school students’ extracurricular of Tri Bhakti Pekanbaru.